Vulnerable geographies: human trafficking, immigration and border control in the UK and beyond. Issue 2 (1st February 2016) - FitzGerald, Sharron A.
Abstract : Human trafficking inspires strong responses from feminists and other interested parties. This article takes the UK anti-trafficking measures as a case study to explore the interaction between discourses of trafficked women's vulnerability to sexual harm, and national vulnerability to external threats such as organized crime. Drawing on feminist engagements with human trafficking and commercial sex, my aim is to contribute to these debates. I explore how the government's moralistic response to trafficking reflects a particular form of regulation that animates new systems of governmentality and biopower. Against this backdrop I attempt to advance feminist perspectives on trafficking by demonstrating the relationality between UK anti-trafficking measures, and its plans to reorganize its regulatory capacity overseas. I suggest an interpretation of UK overseas anti-trafficking measures that foregrounds respatialized border and immigration controls. I show how this kind of regulation works on and through the bodies and behaviours of government actors. I conclude that while aspects of these overseas interventions do go some way to protect trafficked women, they do not operate in isolation of other geopolitical agendas.